2015
DOI: 10.1093/bja/aeu449
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin prophylaxis for postoperative nausea and vomiting in abdominal surgeries: a quantitative analysis of evidence from randomized controlled clinical trials

Abstract: The present analysis provides evidence supporting preoperative gabapentin as a pharmacotherapy for prevention of PONV in patients undergoing abdominal surgeries. Future studies comparing preoperative gabapentin with 5HT3 antagonists are needed to precisely define its role in PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This is clinically meaningful when considering the report that the PONV symptoms can appear up to at least 72 h after discharge from PACU [38]. This finding might be explained in part by the possibility of long-lasting (> possibly 24 h) antiemetic effect of gabapentin [2]. Further clinical trials are required to address this issue.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This is clinically meaningful when considering the report that the PONV symptoms can appear up to at least 72 h after discharge from PACU [38]. This finding might be explained in part by the possibility of long-lasting (> possibly 24 h) antiemetic effect of gabapentin [2]. Further clinical trials are required to address this issue.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study by Achuthan et al [2] of the use of gabapentin in patients undergoing abdominal surgery demonstrated the differential antiemetic efficacy of gabapentin with respect to the use of propofol, either as an induction or maintenance agent. Preoperative gabapentin as pharmacotherapy for preventing PONV was effective when propofol was not used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies suggested that using oral gabapentin (an anticonvulsant) before surgery significantly reduced the incidence of postoperative nausea and vomiting after open cholecystectomy. [3033] It has been suggested that antiemetic effect of gabapentin is caused by reducing the activity of tachykinin neurotransmitter. [2,9] Furthermore, vitamin B6 has been known to possess antiemetic effects since 1942.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent meta-analysis has also identified the benefits of gabapentin with regard to preoperative anxiety and chronic pain at the expense of an increase in sedation. 8 Over the last decade, randomized-controlled trials have been published indicating that gabapentin may also be useful in attenuating the hemodynamic response to intubation.…”
Section: Résumémentioning
confidence: 99%